Contrast sensitivity in patients with diabetes - Mirković, Jelena M; Risimić, Dijana (Medicinski podmladak, 2018)
Introduction: Diabetic retinopathy is a microvascular complication of diabetes. It is a progressive disease that includes following stages: no apparent DR, nonproliferative DR and proliferative DR. Contrast sensitivity is defined as the ability to distinguish details at low contrast levels. Numerous studies have shown that in patients with DR, in stages when visual acuity is normal or only mildly reduced, CS function is significantly affected. Aim: The aim of our study was to examine whether CS is reduced in patients with diabetes, and whether is it significantly lower in diabetic patients compared to healthy subjects. Materials and methods: 20 patients with diabetes treated at Hospital for Eye Diseases, Clinical Center of Serbia and 20 healthy subjects from general population participated in the study. We have conducted case-contol study. To measure CS, we used low-contrast ETDRS chart. Results: CS in diabetic patients was compared with CS in healthy subjects. We also examined CS in diabetics with and without retinopathy. A statistically significant differens was observed between the patients and the control group, both at monocular and binocular vision and the diseased persons had significantly impaired CS function. Regarding the stage of retinopathy, statistical significance existed only in monocular vision, in terms of decreased CS in patients with nonproliferative DR. Our study shows that there is no statistically significant difference in CS in diabetics with hemoglobin A1c lower than 7 and in those with hemoglobin A1c equal or higher than 7. Conclusion: Our research finds that CS in diabetic patients can be greatly impaired, even in early stages of desease, while there are still no retinal abnormalities. In view of the fact that in all of our respondents visual acuity was normal, we conclude that measuring CS, could be good indicator of early vision disorders in diabetic patients. Key concepts: diabetes mellitus, diabetic retinopathy, contrast sensitivity